Assessment of Coagulation and Fibrinolysis in Pre-eclampsia. Issue 5911 (20th April 1974) - Wood, S. M.; Burnett, D.; Picken, A. M.; Farrell, G. W.; Wolf, P.
Abstract : A method is described for distinguishing coagulation from fibrinolysis by three estimates of fibrinogen. This "fibrinogen series" together with plasma antithrombin and urinary urokinase have been compared in pregnant patients with venous thrombosis and pre-eclampsia. Evidence is presented for active coagulation during deterioration of the pre-eclampsia state and for enhanced fibrinolysis during improvement.